2001
DOI: 10.1046/j.1365-8711.2001.04517.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of giant planets in planetesimal discs

Abstract: Planets orbiting a planetesimal circumstellar disc can migrate inward from their initial positions because of dynamical friction between planets and planetesimals. The migration rate depends on the disc mass and on its time evolution. Planets that are embedded in long-lived planetesimal discs, having total mass of $10^{-4}-0.01 M_{\odot}$, can migrate inward a large distance and can survive only if the inner disc is truncated or because of tidal interaction with the star. In this case the semi-major axis, a, o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 68 publications
(130 reference statements)
2
26
0
Order By: Relevance
“…Some authors have also proposed scenarios in which migration and formation were concurrent (Terquem, Papaloizou & Nelson 2000). We refer the reader to Del Popolo et al (2001, hereafter DP1) and Del Popolo & Ekşi (2002, hereafter DP2) for a detailed discussion of the different mechanisms that have been proposed to explain the presence of planets at small orbital distances: (i) dynamical instabilities in a system of giant planets (Rasio & Ford 1996; Weidenshilling & Marzari 1996), (ii) ‘migration instability’ (Murray et al 1998), (iii) tidal interaction with a gaseous nebula (Goldreich & Tremaine 1979, 1980; Ward 1986; Lin, Bodenheimer & Richardson 1996; Ward 1997) and (iv) dynamical friction between the planet and a planetesimal disc (DP1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have also proposed scenarios in which migration and formation were concurrent (Terquem, Papaloizou & Nelson 2000). We refer the reader to Del Popolo et al (2001, hereafter DP1) and Del Popolo & Ekşi (2002, hereafter DP2) for a detailed discussion of the different mechanisms that have been proposed to explain the presence of planets at small orbital distances: (i) dynamical instabilities in a system of giant planets (Rasio & Ford 1996; Weidenshilling & Marzari 1996), (ii) ‘migration instability’ (Murray et al 1998), (iii) tidal interaction with a gaseous nebula (Goldreich & Tremaine 1979, 1980; Ward 1986; Lin, Bodenheimer & Richardson 1996; Ward 1997) and (iv) dynamical friction between the planet and a planetesimal disc (DP1).…”
Section: Introductionmentioning
confidence: 99%
“…The main approximation used in this model is to associate one grain size to a given radius and time. Then, we use the radial distribution of planetesimals predicted by this model to estimate the planet migration, which is computed as in Del Popolo et al (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Levison & Stewart (2001) argued that the ‘standard’ model for the formations of Uranus and Neptune was not correct, and they concluded that Jovian planets most probably experienced orbital expansions. In fact, some indirect evidence, including observations of extrasolar systems, has been found and diverse models have been proposed (Del Popolo, Gambera & Ercan 2001). Planets may migrate outward or inward, depending on the specific dynamical processes that they underwent.…”
Section: Introductionmentioning
confidence: 99%
“…Hot Jupiters are thought not to have formed in their short‐period orbits but to have migrated in from much larger radii early in the history of the Solar system (e.g. Nelson et al 2001; Del Popolo, Gambera & Ercan 2001). According to Burrows et al (2000), the ordinary contraction of the planet under gravity in the first few Myr after formation will be halted, but not reversed, by strong stellar insolation.…”
Section: Introductionmentioning
confidence: 99%